Comprehensive profiling of Rhodiola rosea roots and corresponding products: phytochemical insights and modulation of neuroinflammation in BV2 microglial cell model - Kołtun-Jasion, Małgorzata; Czerwiec, Karolina; Parzonko, Andrzej; Bakiera, Aleksandra; Ożarowski, Marcin; Kiss, Anna Karolina (Frontiers in Pharmacology, 2025)
IntroductionRhodiola rosea L., mainly known within the medicinal plant industry as golden root, Arctic root, or rose root, derives its name from its economic significance, distinctive morphology, and restricted geographical distribution. Extracts from Rhodiola rosea roots/rhizomes are widely used across Europe and Asia as ingredients of traditional herbal medicines and dietary supplements, with numerous claims regarding their adaptogenic effects. With the growing demand for pharmaceutical products that relieve stress-related fatigue and exhaustion, driven by technological advancements and increasing psychophysical challenges, R. rosea has become a highly sought-after resource. However, this heightened demand has also increased the risk of adulteration and the proliferation of low-quality products on the market. The reproducible efficacy and quality of R. rosea preparations are largely dependent on the variable content of key active compounds, such as rosavin, which directly influence product quality. The rapid expansion of the dietary supplement market, coupled with insufficient quality verification of products entering the market, underscores the need for rigorous identification and quality assessment of these products.MethodsThis study aimed to perform a phytochemical analysis of 13 dietary supplements claiming to contain R. rosea using HPTLC and LC-MS techniques and to correlate these findings with their anti-inflammatory activity in an LPS-stimulated BV2 microglial cell model, in vitro.ResultsOur study indicates that nearly 60% of the tested preparations did not contain the declared amount of Rhodiola rosea roots/rhizomes or the characteristic marker compounds associated with this species. Furthermore, rosavin was detected in only 9 out of the 13 analyzed products, with 4 of these containing only trace amounts of this marker compound. Misidentification of R. rosea was most frequently observed among tablet and capsule formulations, whereas products in the form of cut raw material exhibited the highest quality. Moreover, rosavin significantly and dose-dependently inhibited the secretion of interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) in lipopolysaccharide (LPS)-stimulated microglial cells.DiscussionThe identification of R. rosea in only 40% of the preparations underlines that rigorous control and standardisation of herbal supplements are crucial to understanding their therapeutic activity and preventing adulteration.